PENGEMBANGAN CASE BASE LEARNING PADA MATA KULIAH PEREKONOMIAN INDONESIA - Atmani, Hastarini Dwi (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
In this time, teacher centered learning is a methods in part of higher education in Indonsia. This method, students passively receive information.Case base learning is an instructional design model that is a variant of project oriented learning. Cases are factually-based, complex problems written to stimulate classroom discussion and collaborative analysis. This one, students construct knowledge through gathering and synthesizing information and integrating it with the general skills of inquiry, communication, critical thinking, and problem solving. Key words : active learning, case base learning.